Alkaloid, Sterol and Triterpenoids from Glycosmis pentaphylla (Retz.) DC - Ahmed, Iftekhar; Islam, Ridwan; Sikder, Md Al Amin; Haque, Mohammad Rashedul; Al Mansur, Md Abdullah; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Four compounds were isolated from the methanol extract of leaves of Glycosmis pentaphylla. The structures of the isolated compounds were solved as epi-oleanolic acid (1), ?-amyrin (2), spinasterol (3) and arborinine (4) by extensive spectroscopic studies, including high field NMR analyses as well as co-TLC with authentic samples. This appeares to be the first report of their occurrence from Glycosmis species. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21887 Dhaka Univ. J. Pharm. Sci. 13(2): 115-118, 2014 (December)